The Impact of Topic Selection on Writing Fluency: Making a Case for Freedom (Journal of NELTA, 2014)
This study sought to test the hypothesis that topic-selection control influences fluency in writing. A total of 29 second-year university students (9 men, 20 women) in two separate classrooms engaged in a free writing activity using different topics (both teacher-selected and self-selected) in order to determine which approach was more likely to increase writing fluency. Participants’ written output was then textually analyzed for fluency using a type/token formula. A total of 116 samples written by participants over four weeks were examined to measure their writing fluency by counting the total number of unique words produced in a free writing task. Participants’ writing samples were then analyzed by conducting a correlated-samples t-test. The results showed the effect of topic-selection had a statistically significant influence on increasing students’ writing fluency. The results also support the claim that fluency development deserves a prominent role in second and foreign language classrooms and curriculums. DOI: http://dx.doi.org/10.3126/nelta.v18i1-2.10328 Journal of NELTA, Vol 18 No. 1-2, December 2013; 31-40